Transformation of Ibn 'Arabi's Spiritual Values in Contemporary Life - Haqiqatullahil Kholidah; Fathiyaturrahmah Fathiyaturrahmah; Siti Raudhatul Jannah (Eastasouth Institute, 2026)
The development of science and technology in the contemporary era has brought significant convenience to human life, yet it has also triggered a spiritual crisis marked by weakening moral values, growing materialism, and psychological anxiety. The dominance of rationalism distances individuals from the transcendental dimension, leading to a loss of life’s deeper meaning. This situation highlights the urgency of a spiritual approach capable of balancing intellectual advancement with inner fulfillment. This study explores the spiritual values in Al-Futūḥāt Al-Makkiyyah by Ibn ‘Arabi as a response to the spiritual challenges of modern society. The objectives are: (1) to analyze the concept of spiritual values in the work; (2) to examine the social settings influencing Ibn ‘Arabi’s thought; and (3) to investigate the transformation of these values in contemporary life. The research employs a qualitative approach using a character study through library research. Data are collected through symbolic and semantic reading and analyzed using Margrit Schreier’s theory. The findings reveal key spiritual concepts: Wahdat al-Wujud, Insan Kamil, and al-Hubb al-Ilahi. Influencing social factors include class, social roles, cultural norms, religiosity, and political-economic conditions. In modern life, these values transform into moral formation, spiritual awareness, meaningful living, and harmonious relationships between humans, nature, and God